2015
DOI: 10.21273/hortsci.50.3.412
|View full text |Cite
|
Sign up to set email alerts
|

Hot Water Combined with Calcium Treatment Improves Physical and Physicochemical Attributes of Kiwifruit (Actinidia deliciosa cv. Hayward) during Storage

Abstract: Kiwifruit has a short storage life and encounters severe disorders during maintenance mainly as a result of its climacteric behavior. The role of calcium and heat treatment in delaying degenerative processes during storage has been revealed. This study investigated the effects of hot water combined with calcium (Ca) dips on the quality of kiwifruit (Actinidia deliciosa cv. Hayward). Whole fruits were treated with hot water for 5, 10, and 15 minutes at 47 °C, therefore dipped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…On the other hand, Mahmud, Eryani‐Raqeeb, Omar, Zaki, and Abdul‐Rahman () found that the immersion of papayas in calcium chloride affected the skin yellowness and delayed the ripening process. Similar results were obtained for whole and fresh‐cut papaya (Ayón‐Reyna et al, ; Ayón‐Reyna, López‐Valenzuela et al, ; ), kiwifruit (Shahkoomahally & Ramezanian, ), mango (Dessalegn, Ayalew, & Woldetsadik, ), and fresh‐cut apple (Aguayo, Requejo‐Jackman, Stanley, & Woolf, ), where hot water combined with calcium maintained for longer time the initial color of fruit. Comparing with the parameters measured in papaya of the control treatment, HW‐Ca treatment delayed the ripening process, maintained the firmness and color, and decreased the decay rate.…”
Section: Resultssupporting
confidence: 70%
See 4 more Smart Citations
“…On the other hand, Mahmud, Eryani‐Raqeeb, Omar, Zaki, and Abdul‐Rahman () found that the immersion of papayas in calcium chloride affected the skin yellowness and delayed the ripening process. Similar results were obtained for whole and fresh‐cut papaya (Ayón‐Reyna et al, ; Ayón‐Reyna, López‐Valenzuela et al, ; ), kiwifruit (Shahkoomahally & Ramezanian, ), mango (Dessalegn, Ayalew, & Woldetsadik, ), and fresh‐cut apple (Aguayo, Requejo‐Jackman, Stanley, & Woolf, ), where hot water combined with calcium maintained for longer time the initial color of fruit. Comparing with the parameters measured in papaya of the control treatment, HW‐Ca treatment delayed the ripening process, maintained the firmness and color, and decreased the decay rate.…”
Section: Resultssupporting
confidence: 70%
“…This mechanism can explain the best effects on this parameter of both HW and HW‐Ca treatments. It has been reported that HW treatment decreases the expression of enzymes involved in cell wall degradation and ethylene synthesis (e.g., polygalacturonase, pectinmetilesterase, and 1‐aminocyclopropane‐1‐carboxylate (ACC) synthase and ACC oxidase), contributing also with firmness retention (Shahkoomahally & Ramezanian, ; Sharma, Singh, & Pal, ). Moreover, heat treatment increases the solubility of calcium in water and the membrane permeability allowing a better diffusion of calcium ions into the fruit and vegetable cells (Aguayo, Escalona, & Artés, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations